The Social Uses of the Innovation Concept. A Qualitative Approach to the Discursive Logics for the Access to and Use of Information, Communication and Knowledge in Andalusia. - José Manuel Rodríguez Victoriano; Enrique Wulff Barreiro (Universidad de Valencia; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
In the semantic architecture of the society of the knowledge the innovation concept is the fundamental brick. It is an adobe that allows to construct very different discourses frequently opposed between them, in what the purpose of its social use concerns. In the present communication we introduce the motivations for the access and use of the information and the knowledge on the part of the different social sectors in the Andalusian society. The analysis of the efforts of the Andalusian administration to promote the economy of knowledge supposes an opportunity to show the contingency in the reduction of the digital divide on the ground of citizen participation. It proposes a qualitative approach to the knowledge production, management and socialization in Andalusia derived from an research performed by means of personal interviews. Our conclusions indicate how the link with the social development is a priority in the case of the small and medium-sized enterprises, as well as for the social organizations and social movements. It underlines the logic of the economic development in the great companies oriented to the technological innovation, in the European Union research laboratory, and in the Andalusian government organ dedicated to the innovation, science and business. In the university, and the public research institutes area the main point is research. Three positions are identified, the traditional that is reluctant to the processes incorporating information and knowledge, the one that finds in the innovation concept the main motor of the Andalusian system of knowledge and the one that is closely connected with the equality and the social emancipation. – – En la arquitectura semántica de la sociedad del conocimiento el concepto de innovación es el ladrillo fundamental. Es un adobe que permite construir discursos muy diferentes y a menudo contrapuestos en cuanto a la finalidad de su uso social. En la presente ponencia presentamos las motivaciones para el acceso y uso de la información y el conocimiento por parte de los distintos sectores sociales de la sociedad andaluza. El análisis de los esfuerzos de la administración andaluza por promover la economía del conocimiento supone una oportunidad para evidenciar la contingencia de la reducción de la brecha digital en base a la participación ciudadana. Se trata de una aproximación cualitativa a la producción, gestión y socialización del conocimiento en Andalucía a partir de una investigación realizada mediante entrevistas personales. Nuestras conclusiones se\~nalan como la vinculación al desarrollo social prima en el caso de las peque\~nas y medianas empresas, y en el de las entidades sociales y movimientos sociales. Destaca la lógica del desarrollo económico en las grandes empresas orientadas a la innovación tecnológica, el laboratorio de investigación de la Unión Europea, y el órgano del gobierno andaluz dedicado a la innovación, ciencia y empresa. Lo principal es la investigación en el dominio de la universidad y los institutos de investigación públicos. Se identifican tres posiciones, la de tipo tradicional refractaria a los procesos que incorporan información y conocimiento, la que encuentra en el concepto de `innovación' el principal motor del sistema andaluz del conocimiento y la que se vincula a la igualdad y a la emancipación social.
Conference: XVII ISA World Congress of Sociology, Gothenburg Sweden, 11-17 July, 2010; Additional information: Also available as a book in Spanish: https://www.morebooks.de/store/es/book/acceso-y-uso-de-la-informaci%C3%B3n-y-el-conocimiento-en-andaluc%C3%ADa/isbn/978-3-8465-6751-7
Keywords: O32; L2; 330; Innovation; Knowledge society; Andalusia; Qualitative sociology; Wissensgesellschaft; Innovationsakzeptanz